David Meredith's 'Affair with America': Re-reading Helen Midgeley in George Johnston's My Brother Jack. (2nd January 2017) - Dahlstrom, James
ABSTRACT: George Johnston's novel, My Brother Jack, is set in an Australian suburb in Melbourne, the action beginning at the conclusion of the First World War. It is a time period in which American popular culture was rapidly spreading in Australia, threatening the local movie, theatre, music, and publishing industries, and America began displacing Great Britain as the provider of culture forms to Australia. This paper examines the narrator's struggle with his identity as a metaphor for Australia's struggle to maintain a unique cultural identity in the face of America's burgeoning influence. It highlights the similarities between Helen Midgeley – the narrator's wife – and the life he builds with her, and Johnston's perceptions of American popular culture. It further places the narrator's brother Jack in a position to represent a more 'traditional' Australian culture, with his demise a sad acceptance of the changing nature of an Australia that is overrun by America's influence.